(untitled) (Bangladesh Journal of Botany, 2021)
Rumex patientia L. can respond to abiotic stresses and withstand low temperatures. Proline accumulation plays important roles under various abiotic stresses in different plants, specially salinity. P5CS and OAT of plants are key enzymes in the proline synthesis pathway. In the present study, the RpP5cs and RpOat genes of the proline synthesis pathway in R. patientia L. were cloned with full-length cDNAs of 2178 bp and 1401 bp. The expression of RpP5cs and RpOat genes were higher in Russian Щавель Чемпион than Chinese R. patientia × R. tianschanicus cv. Rumex under salinity and alkalinity stress over 0 - 24 hrs. These results could provide insights into sequence structure and differential tolerance in many plants. Bangladesh J. Bot. 50(3): 717-727, 2021 (September) Special